2010
DOI: 10.4238/vol9-2gmr736
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of ecotypic differentiation between populations of the tree species Parapiptadenia rigida due to flooding

Abstract: ABSTRACT. The tree species Parapiptadenia rigida, native to southern South America, is frequently used in reforestation of riverbanks in Brazil. This tree is also a source of gums, tannins and essential oils, and it has some medicinal uses. We investigated flooding tolerance and genetic diversity in two populations of P. rigida; one of them was naturally exposed to flooding. Plants derived from seeds collected from each population were submitted to variable periods of experimental waterlogging and submergence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…A mortality rate similar to the one found in A. sellowiana was reported for P. rigida: 40% of the young plants died following flooding stress (Silva et al, 2010). However, P. rigida is not vulnerable to low-intensity waterlogging, where mortality is associated with long periods of a combination of soil flooding and complete submergence of saplings.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…A mortality rate similar to the one found in A. sellowiana was reported for P. rigida: 40% of the young plants died following flooding stress (Silva et al, 2010). However, P. rigida is not vulnerable to low-intensity waterlogging, where mortality is associated with long periods of a combination of soil flooding and complete submergence of saplings.…”
Section: Discussionsupporting
confidence: 68%
“…Other species use the low oxygen escape syndrome (Bailey-Serres and Voesenek, 2008), an avoidance strategy that facilitates the survival of submerged organs through the development of anatomical and morphological traits that facilitate inward diffusion of CO 2 and O 2 and reduce the resistance for internal gas diffusion, thereby improving underwater photosynthesis and aerobic metabolism. There are also species that combine those strategies in order to cope with different intensities of flooding (Silva et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such cases, the observed genetic distance between populations was positively correlated with their geographic distances. This hypothesis could be verified from the combined analysis of two studies conducted with P. rigida, where two nearby populations (Silva et al, 2010) and eight populations distributed over a long geographic scale (Souza et al, 2011) were evaluated. For nearby populations, the Fst value obtained was only 6.2%, whilst the average F ST between the eight populations was 22.8%, and the correlation between genetic and geographic distance was positive and significant.…”
Section: Effects Of Fragmentation In Natural Populations From Tibagi mentioning
confidence: 92%
“…Briefly, the results showed that some tree species naturally distributed in this river basin but that do not occur in flooded areas, did not tolerate the stress of artificial flooding; also, there was a great variation in the response of the species from wetlands. In addition to this information, the provenance trials, conducted to compare the performance of populations of the same species from areas periodically flooded and non flooded, showed that for the studied species, Luehea divaricata and Parapiptadenia rigida, the plants that originated from populations naturally flooded were more efficient in responding to waterlooging stress (De Carvalho et al, 2008) or tolerated higher levels of stress, which was not tolerated by the plants of the other provenance (Silva et al, 2010). In a similar study with the tree species Aegiphila sellowiana, used plants regenerated from seeds collected in four regions that presented occasional flooding, showing a variation in the response of individual tolerance to waterlogging.…”
Section: Local Adaptation Of Tree Species To Floodingmentioning
confidence: 99%